2021
DOI: 10.1001/jamaoto.2020.3852
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children With Single-Sided Deafness

Abstract: IMPORTANCEIn 2019, the US Food and Drug Administration approved cochlear implantation for children with single-sided deafness (SSD). The absence of robust clinical data specific to pediatric patients to guide shared decision-making and to identify potential advantages is a challenge in family counseling.OBJECTIVE To evaluate the audiological and patient-reported outcomes in children who underwent cochlear implantation for SSD and to assess the association between time of implantation, subjective outcomes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 69 publications
(267 reference statements)
4
85
0
3
Order By: Relevance
“…These changes make extrapolation from earlier studies problematic. Unlike CI patients implanted in the 1980s and 1990s, the majority of whom were profoundly deaf in both ears, today's CI candidates often include adults and children who still retain usable, and in case of single-sided deafness, normal hearing in one ear (Benchetrit et al, 2021 ). Patients with greater overall hearing abilities prior to implantation may expect more from their hearing after implantation, and post-implantation PES scores that indicated an improvement in the past may no longer be sufficiently high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes make extrapolation from earlier studies problematic. Unlike CI patients implanted in the 1980s and 1990s, the majority of whom were profoundly deaf in both ears, today's CI candidates often include adults and children who still retain usable, and in case of single-sided deafness, normal hearing in one ear (Benchetrit et al, 2021 ). Patients with greater overall hearing abilities prior to implantation may expect more from their hearing after implantation, and post-implantation PES scores that indicated an improvement in the past may no longer be sufficiently high.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlear implants are the treatment of choice for a growing number of people afflicted with sensorineural hearing loss beyond the therapeutic capabilities of acoustic amplification with hearing aids (NIDCD, 2021 ). Although CIs were initially approved by the Food and Drug Administration (FDA) for adults with profound hearing loss in both ears (Sladen et al, 2017 ), today's CI candidates may include adults and children who still retain usable, and sometimes normal hearing in at least one ear (e.g., Benchetrit et al, 2021 ). Patients with greater overall hearing abilities prior to implantation may expect more from their implants afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also provided evidence that some adult SSD + CI recipients have improved speech in noise performance secondary to binaural redundancy and binaural squelch (Vermeire & Van de Heyning 2009; Mertens et al 2015). Pediatric SSD + CI patients have shown improvement in SIN tasks as well (Sladen et al 2017; Thomas et al 2017; Zeitler et al 2019; Benchetrit et al 2021; Ehrmann-Mueller et al 2020; Park et al 2021a).…”
Section: Test Batterymentioning
confidence: 99%
“…The 2019 FDA labeling approval for implantation in cases of SSD in children aged 5 and older (MED-EL) was welcomed. Early studies and case reports have indicated benefits in chil-dren, 42 particularly when it comes to hearing in noise [43][44][45][46][47] and localization. 43,48,49 The age limit of 5 years was likely set due to safety, as the clinical trial used for approval did not include young children.…”
Section: Single-side Deafnessmentioning
confidence: 99%